CD4+ T Cells in the Blood of MS Patients Respond to Predicted Epitopes From B cell Receptors Found in Spinal Fluid - Høglund, Rune A.; Bremel, Robert D.; Homan, E. Jane; Torsetnes, Silje Bøen; Lossius, Andreas; Holmøy, Trygve (Frontiers in Immunology, 2020)
B cells are important pathogenic players in multiple sclerosis (MS), but their exact role is not known. We have previously demonstrated that B cells from cerebrospinal fluid (CSF) of MS patients can activate T cells that specifically recognize antigenic determinants (idiotopes) from their B cell receptors (BCRs). The aim of this study was to evaluate whether in silico prediction models could identify antigenic idiotopes of immunoglobulin heavy-chain variable (IGHV) transcriptomes in MS patients. We utilized a previously assembled dataset of CSF IGHV repertoires from MS patients. To guide selection of potential antigenic idiotopes, we used in silico predicted HLA-DR affinity, endosomal processing, as well as transcript frequency from nine MS patients. Idiotopes with predicted low affinity and low likelihood of cathepsins cleavage were inert controls. Peripheral blood mononuclear cells from these patients were stimulated with the selected idiotope peptides in presence of anti-CD40 for 12 hours. T cells were then labeled for activation status with anti-CD154 antibodies and CD3+CD4+ T cells phenotyped as memory (CD45RO+) or naïve (CD45RO-), with potential for brain migration (CXCR3 and/or CCR6 expression). Anti-CD14 and -CD8 were utilized to exclude monocytes and CD8+ T cells. Unstimulated cells or insulin peptides were negative controls, and EBNA-1 peptides or CD3/CD28 beads were positive controls. The mean proportion of responding memory CD4+ T cells from all nine MS patients was significantly higher for idiotope peptides with predicted high HLA-DR affinity and high likelihood of cathepsin cleavage, than towards predicted inert peptides. Responses were mainly observed towards peptides affiliated with the CDR3 region. Activated memory CD4+ T cells expressed the chemokine receptor CCR6, affiliated with a Th17 phenotype and allowing passage into the central nervous system. This in vitro study suggests that that antigenic properties of BCR idiotopes can be identified in silico using HLA affinity and endosomal processing predictions. It further indicates that MS patients have a memory T cell repertoire capable of recognizing frequent BCR idiotopes found in endogenous CSF, and that these T cells express chemokine receptors allowing them to reach the CSF B cells expressing these idiotopes.